Conservation implication and traditional ecological knowledge on trading bird: A case study in Depok bird market in Surakarta, Central Java, Indonesia - FEBRIANA KINANTHI PUTRI; FITRI ALICIA; HELENA JOAN NOVEN; MUCHAMMAD SHOLIQIN; WIDHI HIMAWAN; REVIDO AJI JAVARENDRA; NOR LIZA; RUHYAT PARTASASMITA; JOHAN ISKANDAR; DARLINA MD. NAIM; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putri FK, Alicia F, Noven HJ, Sholiqin M, Himawan W, Javarendra RA, Liza N, Partasasmita R, Iskandar J, Naim DM, Setyawan AD. 2021. Conservation implication and traditional ecological knowledge on trading bird: A case study in Depok bird market in Surakarta, Central Java, Indonesia. Biodiversitas 22: 5636-5647. Bird species have been the most popular animals in Indonesia for such a long time. Therefore, the demand for birds has been rising in urban areas. The bird species are usually traded, including selling and buying activities in urban bird markets. The increase of bird trading in Indonesia also increased Indonesian people's economic and social benefits. Consequently, there is a chance that many bird trading in bird markets are not managed carefully without preventing bird species extinction in rural ecosystems. This paper aimed to assess the conservation status of birds sold and the Traditional Ecological Knowledge (TEK) of bird traders in Depok bird market in Surakarta (Solo), Central Java, Indonesia. The study used a qualitative method with the ethno-ornithological approach. The results showed that the diversity of birds encountered in the bird market of Depok was considered high, 55 species were recorded, representing 29 families. The Indonesian law protects seven bird species while 12 species are considered endemic. Moreover, 8 birds are included in IUCN Red List. The bird naming is based on particular categories agreed on in the local community. Furthermore, social involvement through education and local wisdom might profoundly impact conservation efforts to preserve the bird population.